2019
DOI: 10.1186/s12889-019-6480-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of intergenerational programs on social capital in Japan: a randomized population-based cross-sectional study

Abstract: BackgroundOver the last several decades, social isolation and loneliness among older adults have posed an increasingly urgent challenge due to the rapidly aging population in Japan. To remedy the situation, many communities have introduced intergenerational programs. However, few studies have investigated the benefits of social capital across generations as a result of intergenerational interaction between children and older generations. Therefore, we aim to ascertain the degree to which intergenerational prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 29 publications
4
43
0
Order By: Relevance
“…The results of the current study demonstrated the relationship between loneliness and social capital. Speci cally, older people who lacked social capital concerning social participation, social connection, and reciprocity were more likely to experience loneliness, which was echoed by ndings from previous studies [10,20,25,41]. Similar to our results, Nyqvist et al [10] found that infrequent social connection with neighbours had an increased likelihood of being lonely among older people aged 65-80 years in Western Finland.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The results of the current study demonstrated the relationship between loneliness and social capital. Speci cally, older people who lacked social capital concerning social participation, social connection, and reciprocity were more likely to experience loneliness, which was echoed by ndings from previous studies [10,20,25,41]. Similar to our results, Nyqvist et al [10] found that infrequent social connection with neighbours had an increased likelihood of being lonely among older people aged 65-80 years in Western Finland.…”
Section: Discussionsupporting
confidence: 90%
“…Results from the fth wave of the Survey of Health, Ageing and Retirement in Europe (SHARE) also concluded that more social participation was a protective factor for loneliness and mitigated the impact of unfavorable socioeconomic status among older people [14]. Some studies also suggested that forming and building reciprocal connections or relationships with others could alleviate the impact of some mental health issues, including loneliness [20,42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Effective partnerships that can leverage social connection to prevent heat illness might include health services, neighbourhood and building associations, business communities, faith-based groups, and municipal centres such as libraries or swimming pools (Price et al 2013). The social health of communities would also benefit from interventions to build long-term social capital through community-based interventions such as creating welcoming community designs and intergenerational programming (Murayama et al 2019). For example, Building Resilient Neighbourhoods in Victoria, BC, supports the ability of communities to build and utilize connections for emergency preparedness through "Connect & Prepare" workshops (Building Resilient Neighbourhoods 2019).…”
Section: Social Connection As Intervention During Extreme Heat Eventsmentioning
confidence: 99%